Determinants Influencing The Application of Management Accounting: The Case of Vietnam - NGUYEN, THANH HUYEN; TRAN, MANH DUNG; NGUYEN, XUAN HUNG (The journal of contemporary issues in business and government, 2021)
The study aimed to determine the factors influencing the level of application of management accounting in feed production firms in Vietnam. Data were collected from the survey of 228 feed production firms in Vietnam. The study employs the combination of qualitative and quantitative methods with building multivariate regression models of determinants affecting the application of management accounting in those firms. The results contribute to building a multivariate regression model of factors affecting the application of management accounting in food production firms. Based on the findings, some recommendations are proposed for improving the effectiveness of applying management accounting in Vietnamese food production firms.